Divine Philanthropy and Human Misanthropy. The Abusive Defrocking and the Rehabilitation Process of Metropolitan Anthim of Iberia - Maxim Marian Vlad (Technium Social Sciences Journal, 2020)
Saint Anthim of Iberia was one of the most cultured people of his time. He is a creator of a whole epoch in Wallachian and, in general, Romanian history. A highly learned metropolitan, he was also one the greatest Orthodox theologians of the time, a master of morality and doctrine, and finally a wise politician, who played a great role in the very complex social, political and cultural life of the Wallachian Principality. He harshly criticized the illiteracy and the greed of clergy, Eastern Patriarchs’ craving for wealth and power, and he relentlessly denounced the corruptness and the moral degradation of the ruling classes. His efforts to ally with Russia to liberate Wallachia from the Ottoman yoke led him to conflict with his great contemporary, Constantin Brâncoveanu, and then, even more gratingly, with the Voevoda Nicholas Mavrocordatos (1716-1730), described by some historians of the time as unwaveringly loyal to the Ottomans. The Phanariote Nicholas Mavrokordatos, who was only interested in the Ottoman Empire, replaced the Wallachian princes. Mavrokordatos was suspicious of Metr. Antimos and ordered the metropolitan to resign. Mavrokordatos appealed to Patriarch Jeremiah after Metr. Antimos refused to do so. The Patriarch convened a council of bishops, without any Romanian representation, that condemned the metropolitan to anathema and excommunication. Not satisfied in a finding that denied Metr. Antimos his title of Metropolitan of Hungro-Wallachia, Mavrokordatos order the metropolitan to exile to St. Catherine’s Monastery at Mount Sinai. On September 14, 1716, while en route to his place of exile, Metr. Antimos was ambushed by Turkish soldiers on the bank of the Tundzha River, near Gallipoli, as it flowed through Adrianople, and butchered him. Then, they threw his remains into the river. This brutal action ended the earthly life of a great man who had dedicated his strength, talent, and knowledge to the revival and strengthening of Orthodox Christianity among the people of Wallachia. The faithful Romanian people, considering, from the beginning, the sentence of defrocking as unjust and illegal, not only never stopped honoring Anthim the Iberian as chief priest also after his abusive defrocking, but with the passage of time increased their acts of piety and honor, considering him one of the most worthy hierarchs who pastored the Romanian Orthodox Church and a martyr, who sacrificed his life, with dignity, for the Orthodox faith and for the freedom and independence of the Motherland, which, since his adoption, he served as the most devoted and loving son.